The Effect of Self-Esteem on Students’ Mathematical Communication Skills - Mahani, Ibud; budiyono, budiyono; pratiwi, hasih (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
This study aims to find out between students with high, medium, and low self-esteem in term of better mathematical communication. This type of research is quantitative research. The data analysis technique used was one-way variance analysis with inequivalent cells. The collection of students' mathematical communication data was obtained from the score of mathematical communication tests, and the data of self-esteem was collected through questionnaires. The subjects of this study were the eighth-grade junior high school students in Ponorogo with the high, medium and low schools categories. The results of this study indicate that students with high self-esteem possess better mathematical communication skills compared to students with moderate self-esteem and students with low self-esteem. Students with low self-esteem are having the same level of mathematical communication skills as students with moderate self-esteem.